Deaths of infants subject to forensic autopsy in Estonia from 2001 to 2005: what can we learn from additional information? - Grjibovski Andrej M; Pärna Kersti; Lang Katrin; Väli Marika M (BMC, 2010)
Abstract Background Deaths from childhood injury are a public health problem worldwide. A relatively high proportion of child deaths of undetermined manner in Estonia raises concerns about potential underestimation of intentional deaths, especially in infants. This suggests that more information on the circumstances surrounding death is needed to establish the manner of death correctly and, more importantly, to prevent these deaths. The objective of this study was to detect, describe, and analyze the circumstances around deaths of infants subject to forensic autopsy in Estonia to reveal hidden cases of child abuse and more accurately determine causes of death. Methods Study cases included all infant deaths in Estonia from 2001 to 2005 subject to forensic autopsy at the Estonian Bureau of Forensic Medicine. Additional information was obtained from a series of visits to general practitioners, including characteristics of infant health, family composition, parents' education and employment, living conditions, and circumstances around death as perceived by medical staff in charge of outpatient services for these families. Results The total number of infant deaths in Estonia between 2001 and 2005 subject to forensic autopsy was 98, with 40 (40.8%) deaths attributed to a disease and 58 deaths (59.2%) resulting from injury. Elements of child abuse were involved in as many as 57.7% (95% CI 46.9-68.1) of the deaths for which medical records were available (n = 90). At death, the majority of these cases were registered as diseases or deaths from unintentional injury. Average annual mortality from external causes in Estonian infants, 2001-2005, previously reported by us as 88.1 per 100,000 (95% CI 68.1-113.6) would decrease to 41.0 (95% CI 26.9-57.8). Many infants in the studied group had faced multiple threats and were living in poor hygienic conditions. In a number of cases, they were left alone or looked after by older siblings. Parents' alcohol abuse played an important role in a considerable number of cases. Conclusions Using additional sources of information revealed new information about child abuse not reflected in the cause of death diagnosis. Effective interventions aimed at parent education and improved follow-up of children by medical staff may reduce mortality from external causes among Estonian infants by more than half.